Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/s23198134
|View full text |Cite
|
Sign up to set email alerts
|

IDAF: Iterative Dual-Scale Attentional Fusion Network for Automatic Modulation Recognition

Bohan Liu,
Ruixing Ge,
Yuxuan Zhu
et al.

Abstract: Recently, deep learning models have been widely applied to modulation recognition, and they have become a hot topic due to their excellent end-to-end learning capabilities. However, current methods are mostly based on uni-modal inputs, which suffer from incomplete information and local optimization. To complement the advantages of different modalities, we focus on the multi-modal fusion method. Therefore, we introduce an iterative dual-scale attentional fusion (iDAF) method to integrate multimodal data. Firstl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…A TP (True Positive) result indicated that the actual situation was a positive situation and the prediction was positive, i.e., the prediction was correct, and the same result could be obtained for TN (True Negative), FP (False Positive), and FN (False Negative) results [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…A TP (True Positive) result indicated that the actual situation was a positive situation and the prediction was positive, i.e., the prediction was correct, and the same result could be obtained for TN (True Negative), FP (False Positive), and FN (False Negative) results [ 51 ].…”
Section: Methodsmentioning
confidence: 99%